(untitled) (Intent Research Scientific Journal, 2023)
Integration in education is the establishment of connections between the components of the content within a certain educational system in order to form a holistic view of the world aimed at the development of the learner’s personality and self-development process. Integration is a process that teaches systematization and simplification of complexity in education.